Understanding the microenterprise sector to design a tailor-made microfinance policy for Cape Verde - Baptista, José A.G. (2018)
Two of the central challenges faced by Cape Verde at the present are the high level of unemployment and the increasing proportion of the population living in (relative) poverty. Microenterprise development can be an effective means of addressing both problems in a developing country like Cape Verde, where microenterprises account for about 50% of employment. In this paper we provide a detailed profile of Cape Verdean microenterprises and microentrepreneurs and investigate the relationship between their characteristics and the resort to outside seed capital. We find a cluster of factors—the microentrepreneur’s age, gender, level of education and reason for being self-employed—which influence significantly the probability of being in need for external start-up capital. The policy implications of these findings for the design of a specific microfinance program for Cape Verde are discussed.